Research on Attitude of Young People for Unhealthy Food - Szűcs, Róbert Sándor (The Hungarian Journal of Marketing and Management, 2019)
Childhood obesity received more attention in marketing and public health care in past recent years. 95% of food advertisements promote foods with high level of fats, sugar and/or salt on the television. Influencing children is a marketing, ethical, economic and consumer protection question at the same time. The cognitive component of attitudes demonstrates low level of knowledge in case of foods with high level of fat, salt and/or sugar. Half of the youth do not pay attention to healthy nutrition and considerable part of them does not understand the markings of food labels according to my research. The marketing activity is able to influence the young persons' attitudes in case of unhealthy foods. The result is increasing consumption of unhealthy foods and drastic rise of hygienic expenses.